Modernisasi Pendidikan Islam di Indonesia (Studi Komparasi Mahmud Yunus dan Azyumardi Azra) - Zulfadhilah Zulfadhilah; Rini Rahman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
One of the main aspects of human life is education. This cannot be separated from life, starting from the human being in the womb until returning to the creator. Seeing that there is still Islamic education that does not achieve its goals and does not keep up with the times, therefore the leaders of Islamic education immediately act to resolve this. Mahmud Yunus is an Islamic education figure who seeks to renew Islamic education. In addition, another character who made updates was Azyumardi Azra. Based on this, the researchers are interested in making comparisons or comparisons of the thoughts of the two figures. Researchers will make comparisons or comparisons specifically in terms of modernizing goals, curricula and educational institutions with the research title